Moodle gradebook : set up and customize the gradebook to track student progress through Moodle - Barrington, Rebecca (Community experience distilled., 2012)
A practical book with plenty of step-by-step instructions and informative screenshots to guide you through the many features of gradebook. Moodle Gradebook is for anyone who uses Moodle as a course instructor. You will need to know the basic functions of using and navigating Moodle, but no prior knowledge of the grades functions will be required.